Paradoks Soft Diplomacy Amerika Serikat: Diplomasi Budaya melalui Program AMINEF Terhadap Kebijakan Imigrasi Restrikti - Pahla Ayuningtyas, Winda Eka; Novianti, Sarah; Wicaksana, Hendika Dwinanda; Pertiwi, Gema; Aprina, Fitria Hani; Dewindaru, Deanda; Rospitasari, Marina; Hesti, Chomariyana Kartika; Sholihah, Lailatus (Universitas Syiah Kuala, 2025)
Paradox of the United States soft diplomacy through the American Indonesian Exchange Foundation (AMINEF) as a tool of cultural diplomacy amid increasingly restrictive immigration policies. While the U.S. promotes openness, multiculturalism, and international collaboration through programs such as Fulbright and the Community College Initiative, its stringent immigration policiesparticularly since the Trump era and beyond the pandemiccontradict the nations image as a defender of freedom and inclusivity. Using a qualitative, literature-based approach and critical discourse analysis, this research explores how soft diplomacy operates as a foreign policy strategy to sustain American cultural hegemony in Indonesia. The findings indicate that, despite restrictive immigration measures, AMINEF remains effective in fostering cultural diplomacy and enhancing the U.S. image in Indonesia. This paradox underscores Americas attempt to balance domestic priorities (security and nationalism) with global ambitions (cultural and political influence).